Acceleration of carbon ions to high energies by a multi-PW laser. (March 2019) - Tchórz, P; Badziak, J; Domański, J; Marchwiany, M
Abstract: Extreme Light Infrastructure (ELI) is a large-scale European project, still in the development stage, offering parameters of laser drivers required for multiple applications (femtosecond pulse duration, ultra-relativistic laser intensities ∼ 10 22 - 10 23 W/cm 2 ), however studies of ion acceleration in the given intensity regime are still in the very early stages and require a deeper understanding of the processes occurring during laser-matter interactions to maximize the efficiency of ion acceleration. The purpose of this work is a numerical examination of the properties of carbon ion beams produced during the interaction of an ultra-intense laser beams (of intensities ∼ 10 21 – 10 23 W/cm 2 and pulse duration order of femtoseconds, predicted to be available at ELI-NP, Romania) with C 12 target. The dependence of ion beam parameters, such as intensity, energy spectrum, maximum and average ion energy and spatial distribution of ion charge density, on laser pulse parameters (mainly intensity) and the target thickness is investigated. The possibility of generation of high intensity, GeV energy ion beams in the foregoing conditions is demonstrated. The obtained results can be useful for research in high energy-density physics, nuclear physics or medical applications of ion beams.